2001
DOI: 10.1007/bf02410104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature pre-treatment of transplants from in vitro produced potato plantlets on transplant growth and yield in the field

Abstract: SummaryIn vitro produced potato plantlets, cvs Gloria and Spunta were planted in soil and exposed to day/night temperatures of 18/12 or 26120 "C for 14 days. They were then transplanted into the field in two experiments to assess after-effects of temperature on the performance of shortcycle crops. Accumulated intercepted radiation (AIR) was calculated from ground cover and incoming radiation, and dry matter production and fresh tuber yield were frequently recorded. Pre-treatment at 26/20 ~ caused higher leaf a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
1
5
1
2
Order By: Relevance
“…Leaf area at the end of the transplant production phase was larger for transplants raised at higher than at lower temperature (Table 3), and so was the initial aboveground leaf area in the subsequent tuber production phase (Table 4). This agrees with results from Tadesse et al (2001). No significant effects of temperature during transplant production on leaf area were present anymore at the end of the tuber production phase (Table 4).…”
Section: Boosts and Shocks After Transition To A New Phasesupporting
confidence: 91%
See 1 more Smart Citation
“…Leaf area at the end of the transplant production phase was larger for transplants raised at higher than at lower temperature (Table 3), and so was the initial aboveground leaf area in the subsequent tuber production phase (Table 4). This agrees with results from Tadesse et al (2001). No significant effects of temperature during transplant production on leaf area were present anymore at the end of the tuber production phase (Table 4).…”
Section: Boosts and Shocks After Transition To A New Phasesupporting
confidence: 91%
“…However, individual plants pre-cultured at higher temperature (Table 4) had higher fitted A-values and a smaller fitted increment in leaf area (C), which agrees with the tendency of a less strong increase in leaf area for transplants raised at higher temperature (Figure 6). These results, however, were not consistent with a higher light interception found for field crops from transplants grown at a higher temperature (Tadesse et al, 2001). A higher temperature during transplant production also resulted in higher leaf numbers at the end of the transplant production and at the beginning of the tuber production phases.…”
Section: Boosts and Shocks After Transition To A New Phasecontrasting
confidence: 78%
“…In order to have any effect, conditions during transplant production therefore must be changed to non‐inducing for more than 11 days up to 18 days (3 weeks minus 3 days of hardening). This probably explains why Tadesse et al (2001 b ), studying the effect of temperature during production of transplants grown for 2 weeks (with 12 days of different conditions), mainly found effects on leaf area and radiation interception of the crops but only limited effects on the degree of dry matter partitioning to tubers.…”
Section: Discussionmentioning
confidence: 99%
“…Jones, 1988; Struik & Lommen, 1990) or first raised to transplants, which are then transplanted into the field (e.g. Tadesse et al , 2001a, b). Glasshouse‐raised transplants from very early cultivars sometimes show a poor performance after transplanting into the field (Haverkort et al , 1991; Lommen, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that various environmental and endogenous factors influence tuberization . A large number of studies have shown that short photoperiod, high light intensity, low temperature, low nitrogen levels and high sucrose levels can promote tuberization (Dobránzki et al 1999, Tadesse et al 2001, EL-Sawy et al 2007, Dobránszki and Tábori 2010. Phytohormones also play a crucial role in regulating the morphological events of tuberization (Aksenova et al 2012, Roumeliotis et al 2012.…”
Section: Introductionmentioning
confidence: 99%